2010
DOI: 10.4141/cjas09048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary citric acid, flavomycin and their combination on the performance, tibia ash and immune status of broiler

Abstract: . W. 2010. Effect of dietary citric acid, flavomycin and their combination on the performance, tibia ash and immune status of broiler. Can. J. Anim. Sci. 90: 57Á63. The goal of this research was to investigate the effect of citric acid (CA), the antibiotic growth promoter flavomycin (FL) and their combination on the growth performance, tibia ash and immune status of broilers. One hundred and sixty straight run day-old broiler chicks (Hubbard Classic) were randomly distributed into four dietary groups, with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
9
31
1
4
Order By: Relevance
“…Some studies have shown limited or no benefit in terms of growth or carcass yield of supplying flavomycin (e.g. Haque et al 2010). In contrast to this study, including the same probiotic as used in the current study has been found to reduce growth rates (e.g.…”
Section: Resultscontrasting
confidence: 70%
“…Some studies have shown limited or no benefit in terms of growth or carcass yield of supplying flavomycin (e.g. Haque et al 2010). In contrast to this study, including the same probiotic as used in the current study has been found to reduce growth rates (e.g.…”
Section: Resultscontrasting
confidence: 70%
“…Nutrient digestibility was also improved in birds fed Flavomycin alone but this improvement in digestibility was not reflected in improved performance in the current experiment. Similar results were reported by Haque et al (2010).…”
Section: Discussionsupporting
confidence: 82%
“…Regardless of the inclusion levels of citric acid, half of the acid-supplemented groups reported significant increase in body weight gain (Chowdhury et al ., 2009;Haque et al ., 2010;Nourmohammadi et al ., 2010;Salgado-Tránsito et al ., 2011). However, only two experiments reported significant improvements in feed intake (Haque et al ., 2010;Nourmohammadi et al ., 2010) and feed efficiency (Chowdhury et al ., 2009;Salgado-Tránsito et al ., 2011). It is postulated that excessive amounts of dietary citric acid inclusion may compromise performance because two experiments using 60 g/kg citric acid in diets reported significant decreases in body weight gain.…”
Section: Citric Acidmentioning
confidence: 99%
“…It is postulated that excessive amounts of dietary citric acid inclusion may compromise performance because two experiments using 60 g/kg citric acid in diets reported significant decreases in body weight gain. (Patten and Waldroup, 1988;Alçiçek et al, 2004;Leeson et al, 2005;Gunal et al, 2006;Hernández et al, 2006;García et al, 2007;Paul et al, 2007;Biggs and Parsons, 2008;Pirgozliev et al, 2008;Samanta et al, 2008;Al-Kassi and Mohssen, 2009;Ao et al, 2009;Bozkurt et al, 2009;Chowdhury et al, 2009;Kim et al, 2009;Mahdavi and Torki 2009;Panda et al, 2009a,b;Haque et al, 2010;Nourmohammadi et al, 2010;Smulikowska et al, 2010;Esmaeilipour et al, 2011;SalgadoTránsito et al, 2011;Aghazadeh and Tahayazdi, 2012;Nourmohammadi et al, 2012;Świątkiewicz and Arczewska-Wlosek, 2012). 2 Detailed information for each organic acid was provided in the Tables 5 through 9.…”
Section: Citric Acidmentioning
confidence: 99%